PENGARUH DIVIDEND OMISSIONS TERHADAP RISIKO INVESTASIDAN PROFITABILITAS - NUR FADHILLAH, DYAH (Jurnal Akuntansi AKUNESA, 2017)
Dividend omissions tend to increase from year to year. In the phenomenon of dividend omissions investors generally respond negatively as investors assume that companies are experiencing liquidity difficulties. This study aims to examine and analyze the effect of dividend omissions on investment risk and profitability in the company go public in Indonesia. Investment risk is measured by standard deviation, while profitability is measured by ROA (Return OnAssests). This study used a sample of 88 companies listed on the Indonesia Stock Exchange during the study period 2009-2015. Data were analyzed using MANOVA (Multivariate Analysis of Variance) analysis method. This study found that companies that do dividend omissions have ROA (Return On Assets) lower than companies that do not dividend omissions. In addition, it was found that a large investment risk in firms that did dividend omissions on thesamples under study. Keyword: Dividend omissions, investment risk, standard deviation, and ROA (Return On Assests).